Annotated record of the detailed examination of Mn deposits offshore the island of Oahu, Hawaii Archipelago - James E Andrews (PANGAEA, 1972)
Occurrences and associations of ferro-manganese deposits at relatively shallow depths in the Hawaiian Archipelago were revealed by a series of cruises on the R/V Teritu. The deposits are accreting principally on the three prominent terrace levels around all of the Islands-at 400 to 800 meters, 1200 to 1600 meters, and 2400 meters as crusts and pavements. In some instances, examples of deposits at low depth demonstrate the rapid growth of ferro-manganese oxides and the importance of seed material for manganese coating to grow on artificial seeds. A large number of iron and steel samples encrusted with ferromanganese deposits have been collected by divers during the past year off Oahu beaches.
Supplement to: Andrews, JE (1972): Distribution of manganese nodules in the Hawaiian Archipelago. in: Manganese Nodule Deposits in the Pacific, Symposium/Workshop Proceedings, Honolulu, Hawaii, October 16-17, 1972, State of Hawaii, Honolulu, Hawaii, USA, 61-65, https://store.pangaea.de/Projects/NOAA-MMS/Andrews_1972.pdf